ANALISIS PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS IV SDN KEBONCAU IV PADA MATERI PECAHAN - Siti Sholikha; Yeni Nuraeni; Moh. Iqbal Firdaus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the mathematical conceptual understanding of fourth-grade students at SDN Keboncau IV on fraction material. This research employed a descriptive qualitative approach. The research subjects consisted of four students selected based on their ability categories, namely two students in the low category and two students in the high category. Data were collected through tests, interviews, and documentation. Data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results of the study indicate that students in the low category still experienced difficulties in determining equivalent fractions, using comparison symbols correctly, providing reasons for their answers, and applying fraction concepts in solving word problems. Meanwhile, students in the high category were able to understand fraction concepts well, including determining fraction values, comparing fractions, identifying equivalent fractions, presenting fraction representations in the form of pictures, and solving word problems related to fractions. In addition, the findings revealed that the use of pictures helped students understand fraction concepts better than questions presented in symbolic form or word problems.